Angry animals - Arnold, Nick; De Saulles, Tony; Gates, Phil (London : Scholastic, 2009)
Twenty titles from the best-selling series, presented in a bulging boxed set. Features all the best-selling Horrible Science titles from A-Z--well from Blood, Bones and Body Bits to Vicious Veg! --
Q
Title, Horrible science, is in each volume and on each side of case and case bottom. Various phrases are on case top and sides, e.g., Bulging box of books, 20 brilliant books in one bulging box, and Science with the squishy bits left in!
All volumes by Nick Arnold except for "Evolve or Die" by Phil Gates. All volumes are illustrated by Tony De Saulles.
Contents indicated on side of case.
Each volume contains own index.
b
b
Keywords: Science -- Juvenile literature; Science -- Study and teaching (Primary)